Kaizen: the key to Japan's competitive success - Imai, Masaaki (New York, 1986)
"For the professional manager or student of management, a comprehensive handbook of 16 Kaizen management practices that can be put to work. KAIZEN uses more than 100 examples in action and contains 15 corporate case studies."